Efficient Coagulation Removal of Fluoride Using Lanthanum Salts: Distribution and Chemical Behavior of Fluorine - Zhong, Xiaocong; Chen, Chen; Yan, Kang; Zhong, Shuiping; Wang, Ruixiang; Xu, Zhifeng (Frontiers in Chemistry, 2022)
La-loaded absorbents have been widely reported for fluoride removal due to the strong affinity of La3+ towards fluoride ion. Herein, chemical removal of fluoride from flue gas scrubbing wastewater using lanthanum salt is investigated. The retaining free F- concentration, phase composition and morphology of filtration residues, and the distribution of fluorine have been investigated using ion-selective electrode, analytical balance, scanning electron microscopy, and X-ray diffractor. The results show that at La/F molar ratio ≥ 1:3.05, the majority of fluorine exists as LaFx3-x complexes, leading to the failure of fluoride removal. At 1:3.20 ≤ La/F molar ratio ≤ 1:3.10, the formation of LaF3 is facilitated. However, co-existing LaFx3-x tends to absorb on the surface of LaF3 particles, leading to the formation of colloidal solution with large numbers of LaF3·LaFx3-x suspended solids. At an optimized La/F molar ratio of 1:3.10, a fluoride removal of 97.86% is obtained with retaining fluorine concentration of 6.42 mg L-1. Considering the existing of positively charged LaFx3-x and LaF3·LaFx3-x, coagulation removal of fluoride is proposed and investigated using lanthanum salts and negatively charged SiO2·nH2O colloidal particles, which is in-situ provided via Na2SiO3 hydrolysis at pH near 5.5. At a La/F molar ratio of 1:3.00 and Na2SiO3 dose of 0.50 g L-1, a fluoride removal of 99.25% is obtained with retaining fluorine concentration of 2.24 mg L-1. When Na2SiO3 dose increases to 1.00 g L-1, the retaining fluorine concentration could be further reduced to 0.80 mg L-1.